Tinjauan Euthanasia dalam Perspektif Hukum Islam dan Hak Asasi Manusia - Darnia Darnia; Fuad Farawansyah; Dirgi Septian Darmajid; Kurniati Kurniati (CV. Lenggogeni Data Publishing, 2024)
Euthanasia is an attempt to end a person's life when they experience incurable pain, in order to end their suffering. In Indonesia, euthanasia cannot be carried out and is an illegal act. Both positive law and the medical code of ethics stipulate that euthanasia is not permitted. When studied from the perspective of Islamic law, it is regulated that active euthanasia is an act that is forbidden and is threatened by Allah SWT with the punishment of hell for those who do it. The author is of the opinion that Euthanasia is considered a criminal offense in Indonesia because it is a form of crime against life which is regulated in Article 344 of the Criminal Code (Criminal Code/KUHP: